1996
DOI: 10.1097/00004647-199601000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Projection from the Basal Forebrain and Cerebral Glucose Metabolism in Rats: A Dynamic PET Study

Abstract: To investigate the influence of cholinergic projections from the basal forebrain on cerebral cortex metabolism, we evaluated the cerebral metabolic rate of glucose (CMRGlu) after selective inhibition of cholinergic neurons in the rat basal forebrain using the pyruvate dehydrogenase complex inhibitor 3-bromopyruvic acid (BPA), and compared the results with those obtained after lesioning the basal forebrain with ibotenic acid, as well as with those from a sham-operated control group. CMRGlu was measured using po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Therefore, a differential regulation of cerebral blood flow and metabolism may be assumed. In recent reports, a remote neuronal control of metabolism has been described for cortical areas that are metabolically influenced by the basal forebrain (40). The results of our group point toward a similar mechanism in this model: The high synchronized activity in the motor cortex is associated with an increase of metabolism mainly in the nucleus posterior (35) of the thalamus, which sends diffuse inputs to the somatosensory cortical areas.…”
Section: Discusseonsupporting
confidence: 68%
See 1 more Smart Citation
“…Therefore, a differential regulation of cerebral blood flow and metabolism may be assumed. In recent reports, a remote neuronal control of metabolism has been described for cortical areas that are metabolically influenced by the basal forebrain (40). The results of our group point toward a similar mechanism in this model: The high synchronized activity in the motor cortex is associated with an increase of metabolism mainly in the nucleus posterior (35) of the thalamus, which sends diffuse inputs to the somatosensory cortical areas.…”
Section: Discusseonsupporting
confidence: 68%
“…12, 1998 has been suggested that local vasoactive factors play a role on a short-term, dynamic basis, and capillary density involved on a long-term, static basis (39). Factors participating in coupling of these two parameters include ion concentrations, blood-gas tension, neurotransmitters (40), neuropeptides, and local neuronal vascular control.…”
Section: Discusseonmentioning
confidence: 99%
“…Typically, glucose use was depressed 3-4 days postexcitotoxin-lesion, but recovered to basal levels within 4 weeks after unilateral lesions, and 4 months following bilateral lesions despite sustained ChAT deficits (9,37,44,47,60,61,80). This functional recovery most likely reflects the lack of cholinergic selectivity of these lesion paradigms, leading to incomplete cholinergic denervation.…”
Section: Reductions Of Cerebral Glucose Metabolism After Cholinergic mentioning
confidence: 99%
“…Hence glucose use changes seen 18 weeks postcholinergic neuronal loss reflect alterations in well organized, functional pathways associated with the basal forebrain cholinergic system. Several previous studies in both rats and baboons used different lesion paradigms to assess glucose utilization after disrupting BF cholinergic projections (9,37,44,47,60,61,80). However, these investigations were compromised by the lack of a discrete, selective cholinotoxin.…”
Section: Reductions Of Cerebral Glucose Metabolism After Cholinergic mentioning
confidence: 99%
“…Evidence also exists for the cholinergic system's role in the regulation of CBF in adults. Cholinergic neurons in the basal forebrain play a role in the regulation of CMR (13), and injection of the cholinergic agonist carbachol into the substantia innominata increases CBF in rats. This effect can be blocked in some cortical regions by systemic treatment with scopolamine, a cholinergic antagonist (14).…”
mentioning
confidence: 99%